A nonlinear M-shaped tri-directional piezoelectric energy harvester. (8th March 2021) - Chen, Keyu; Gao, Fei; Liu, Zheyuan; Liao, Wei-Hsin
Abstract: In this paper, we design and experimentally validate a geometric nonlinear M-shaped tri-directional piezoelectric energy harvester. This harvester adopts a single structural design, which consists of a proof mass and a beam bent into an M shape with both ends fixed. Through structural parameter modification, the vibration directions of the first three resonant modes can be nearly orthogonal, which is beneficial to achieve tri-directional energy harvesting. Finite element analysis is performed to guide the design and analyse the working effectiveness of the proposed harvester. The influence of the geometric parameters on the nonlinear stiffness is investigated to broaden the bandwidth of energy harvesting. In the experimental validation, an obvious hardening effect can be observed in vertical excitation at 0.3 m s −2 base acceleration. On the other hand, the power output of the harvester in three directions is in similar level, indicating the capability of tri-directional energy harvesting.